An introduction to social psychology - Hewstone, Miles; Stroebe, Wolfgang; Jonas, Klaus (BPS textbooks in psychology, 2012)
"The fifth edition of this highly successful text, An Introduction to Social Psychology has been fully revised and updated. Accessibility for students has been improved, including better illustrations, greater use of colour and a more approachable format, as well as a wealth of online resources. Combining its traditional academic rigour with a contemporary level of cohesion, accessibility, pedagogy and instructor support, the fifth edition of An Introduction to Social Psychology provides the definitive treatment of social psychology"-- Provided by publisher.